Haemophagocytic lymphohistiocytosis in patients treated with immune checkpoint inhibitors: analysis of WHO global database of individual case safety reports - Alessandro Ceschi; Roberta Noseda; Raffaela Bertoli; Laura Müller (Journal for ImmunoTherapy of Cancer)
Background Immune checkpoint inhibitor (ICI) use in clinical practice has unravelled a spectrum of immune-related adverse events (irAEs) due to immune system hyper-activation. ICI-related haemophagocytic lymphohistiocytosis (HLH) has been recently outlined in single case reports, raising a concern about the need of increasing our knowledge on this rare yet life threatening ICI haematological toxicity.Methods To determine ICI-related HLH clinical, haematological, and coagulation features, its timing and outcome, concurrent irAEs and concomitant infections, we performed a retrospective observational cross-sectional study and queried VigiBase, the WHO global database of suspected adverse drug reactions (ADRs), on September 30th, 2018. We retrieved the individual case safety reports reporting HLH in association with ipilimumab, nivolumab, pembrolizumab, atezolizumab, avelumab or durvalumab, gathered in the database starting from the ICIs’ approval dates by the US Food and Drug Administration. The main outcome measures were co-suspected drugs, concurrent irAEs, HLH clinical, haematological and coagulation features, concomitant infections, HLH median time to onset and outcome.Results Among 49′883 ICI-related ADRs collated in VigiBase as of September 30th, 2018, HLH was reported in 38 cases of which 34 (90%) mentioned ICIs as the solely suspected drugs. ICI-related HLH showed clinical, haematological and coagulation features similar to those of HLH with different etiology. Concurrent irAEs occurred in 5 (13%) patients and 6 (16%) reported concomitant viral infections. 31 (82%) cases defined ICI-related HLH outcome, which resolved in 19 (61%) cases. HLH developed a median of 6.7 weeks after initiation of ICI treatment (IQR 2.9–15.4, n = 18, 47%).Conclusions By evaluating the largest cohort of ICI-related HLH cases, we observed that ICI-related HLH arises with a delayed timing with respect to initiation of ICI treatment, and usually presents without other irAEs and concomitant infections. Keeping in mind these findings, clinicians should consider ICIs’ involvement in the onset of HLH whenever they diagnose a disease of this group of syndromes in cancer patients treated with ICIs.